Caputo Fractional Order Nonlinear Incidence HIV Infection Model with Optimal Control (Contemporary Mathematics, 2024)
Examining mathematical models is a crucial aspect of research in comprehending the dynamics and managing the transmission of Human Immunodeficiency Virus (HIV). This study presents a Caputo fractional order HIV infection model with optimal control. We demonstrate that this model exhibits solutions that are always nonnegative. Additionally, we provide a comprehensive examination of the elasticity of both zero disease and viral-persistence equilibrium location. We also delve into the numerical method proposed by Atanackovic and Stanckovic for solving Generalized Inverse Method and provide numerical simulations to validate the findings.
Keywords: caputo fractional differential equations; stability; sensitivity; optimal control; numerical solutions